Impact of Climate Change on Economic Development Associated with Water Scarcity: A Review - Sultana, Mst. Suraiya; Mostafa, M. G. (Journal of Sustainability and Environmental Management, 2023)
Concerns about climate change-induced water scarcity has the potential to hinder development activities. This study aimed to investigate the impact of climate change-related water scarcity on economic development. The study was based on a comprehensive analysis of secondary data obtained from online various sources, including websites, journals, and publications. The analysis revealed a robust inverse correlation between economic growth and water shortages resulting from climate change, with adverse consequences observed in multiple sectors, including health, energy, and agriculture, among others. This study recommends prioritizing the development of water infrastructure, enhancing groundwater replenishment, promoting wastewater recycling and rainwater harvesting practices, improving agricultural techniques, and adopting cutting-edge water conservation technologies to address water scarcity and foster sustainable water resource management.